Towards a Renewed Sociology of Agriculture and Food: Editorial Introduction - Loconto, Allison Marie; Psarikidou, Katerina; Marris, Claire (The International Journal of Sociology of Agriculture and Food, 2022)
“The Sociology of Agriculture and Food” (SAF) is a polysemic phrase. It represents a sub-discipline within the field of sociology, an epistemic community and a network of colleagues. This, the first editorial introduction of the new IJSAF editorial team, initiates what will be a four-year journey on the path of renewing the sociology of agriculture and food. This short essay provides the backstory for the team’s mandate, it introduces the research themes and enigmas that interest the editorial team and it positions the articles in this first issue as a first engagement with the renewed scientific program. It also introduces the new approach to better integrating the activities of the scholarly society (RC40) with the journal, in an attempt to increase the geographic and epistemic inclusivity of both.